(untitled) (Medico Legal Update, 2020)
Introduction: The sensation to cold, shake occurrence and shivering are events that are commonly developed following general anesthesia administration postoperatively. Hypothermia has been considered as the most frequent outcome of surgery underwent by anesthesia. Inadvertent hypothermia has been taken into account as common side effect in the postoperative period immediately and it is related to wide impairments and anomalies of different body organs. Concentration on predictive factors of hypothermia would be important to reduce the incidence rate and correct preventable unnecessary risks for patients in the health settings following surgical operations. The aim of study is to assess the magnitude and associated factors of postoperative hypothermia recovery room in patients underwent general anesthesia. Methods: A hospital based prospective cross-sectional study was conducted on200patients with different age groups of both genders who underwent a scheduled non-cardiac surgery and general anesthesia consecutively during the period between the October 1stand the November1st2016. Results: The study revealed that the overall core hypothermia in the study sample was31%. The study showed that the post-operative temperatures decreased statistically significantly in all study patients and separately in adults, children, males, or females P<0.001. The study also revealed that the operation duration(p=0.045)and pre-operative temperature P<0.001were predictors of post-operative hypothermia in study sample. Conclusions: The incidence of hypothermia among study sample was not so high. A significant reduction in core body temperature of patients between pre and post-operation times was found. Those patients with longer operation duration, lower room temperature, and lower pre-operative temperature were at more risk of post-operative hypothermia.